Determinants of anti-trafficking policies: evidence from a new index - Cho, Seo-Young; Dreher, Axel; Neumayer, Eric (The Scandinavian journal of economics, 2014)
We develop an index measuring the three main dimensions - prosecution, protection, and prevention - of the anti-trafficking policies of the governments of up to 180 countries over the 2000−2010 period. Overall, developed countries perform better than the rest of the world; compliance with prosecution policy is highest, while governmental efforts to protect victims of human trafficking remain weakest. We employ the new indices to investigate which factors determine anti-trafficking policies. We find that compliance with anti-trafficking policies significantly decreases with corruption and is higher in countries that also respect the rights of women. We also find some tentative evidence for spatial dependence in anti-trafficking policies.